Molecular connections between inflammation and social determinants of health - Vijendra, Aditi; Kunkle, Claire; Jordan, Jalin; Erickson, Anna; Osei-Karikari, Kingsley; Ratley, Grace; Myles, Ian A. (Frontiers in Epidemiology, 2025)
Chronic inflammatory diseases such as autoimmune disorders, cancer, cardiovascular diseases and neurodegenerative disorders are a significant cause of morbidity and mortality in the industrialized world. Socioeconomically disadvantaged communities bear a disproportionately high burden of these inflammatory diseases. This review synthesizes evidence linking various domains of the Social Determinants of Health (SDoH)—economic stability, education access and quality, healthcare access and quality, neighborhood and built environment, and social and community context—to inflammatory pathways and mechanisms. Across domains, biological mechanisms such as cytokine dysregulation, toll-like receptor (TLR) activation, hypothalamic-pituitary-adrenal (HPA) axis alterations and gut microbiome disruption act together to sustain proinflammatory states that drive adverse health outcomes in marginalized communities. Although causality is obscured by interrelated determinants, identifying inflammation as a shared pathway between various determinants highlights the need for structural interventions to reduce chronic disease burden.